Molecular Dynamics Simulation on Structure and Dielectric Permittivity of BaTiO3/PVDF Composites. (22nd September 2021) - Bo, Ruitian; Liu, Junwang; Wang, Chunfeng; Wang, Yongliang; He, Peigang; Han, Zhidong
Abstract : Molecular dynamics (MD) simulation was performed to investigate the structure and dielectric permittivity of poly(vinylidene fluoride)- (PVDF-) based composites with different contents of barium titanate (BT). The β -phase PVDF model with 100 structural units and the spherical BT particle model with a radius of 0.495 nm were built and applied in the initial models with three PVDF macromolecular chains and BT particles for the MD simulations of the BT/PVDF composites. The influences of BT content on the morphological structure, the free volume fraction, and glass transition temperature of the composites were explored according to the simulated results and the experimental ones of X-ray diffraction (XRD) and scanning electron microscope (SEM). A model was proposed to predict the static dielectric permittivity of the composites, the results of which were compared with the Cole-Cole fitting results of dielectric spectroscopy. Attempts were made to reveal the structure evolution and the micropolarization mechanism with the increasing content of BT.